Estudo fitoquímico de Wissadula periplocifolia (L.) C. Presl (Malvaceae) e desenvolvimento de metodologia analítica para quantificação do seu marcador químico - Teles, Yanna Carolina Ferreira (2015)
Wissadula periplocifolia (Malvaceae), commonly know in Brazil as “malva amarela”, is popularly used to treat snake bites and bee stings. A phytochemical study on its aerial parts using chromatographic techniques has led to the isolation of chlorophyll derivatives, terpenoids, phenolic acids and thirteen flavonoids, among them methoxylated flavones, glucosyl flavonoides and sulfated flavonoids, notably the new compounds: 5 –hydroxy -4’- methoxy - 7-O- sulphate flavone; 5,7 –di- hydroxy -4’- methoxy- 8-O- sulphate flavone; 5,7,4’–tri- hydroxy - 8-O- sulphate flavone; 5,8 –di- hydroxy -4’-methoxy- 8-O- sulphate flavone and 5,7,4’ –tri- hydroxy -3’- methoxy- 8 O- sulphate flavone. The isolated compounds were characterised by spectroscopic analysis, such as 1D and 2D NMR and LC-HRMS. A preliminary assay to evaluate the antibacterial activity of W. periplocifolia phases showed that the dichloromethane, ethyl acetate and n-butanol fractions were active against Enterococcus faecalis. The flavonoids tiliroside and 7,4’-di-O-methylisoscutellarein showed anti-inflammatory activity by inhibiting neutrophils recruitment in a mice model. Tiliroside was selected as W. periplocifolia chemical marker and an analytical methodology was developed and validated in order to quantify by HPLC the tiliroside content in W. periplocifolia ethanol extract. Using this methodology it was detected the presence of 3.5% of tiliroside in W. periplocifolia ethanol extract.